Daisy-head Mayzie - Seuss, Dr. (New York : Random House, 1994)
Young Mayzie McGrew becomes a worldwide sensation when a daisy grows out of the top of her head, and everyone attempts to get rid of it.
1 3 6 7 8 9 10 11 12 13 15 18 19 20 23 25 27 29 30 31 33 36 39
Keywords: Daisies -- Fiction; Humorous stories; Stories in rhyme